The Place Of Turkish Culture Of The Life In Housing Design “Example Of Turkish Houses In Cyprus During The Ottoman Period" - Turkan, Zihni (The Turkish Online Journal of Design Art and Communication, 2016)
The house has been a sanctuary as the sum of places designed for the functions of life and enabling the family, the smallest of communities, to live together. People’s needs for shelter can be holistic in containing physical adequacy of living quarters as well as their social and psychological adequacies. Various criteria, such as the number of family members, spatial needs, inner-outer space relations, auxiliary spaces, construction quality, and conditions of comfort are programmed and shaped within the life cultures of communities. Spaces in Traditional Turkish House, shaped with the Turkish life culture, are designed in accordance with the living styles and traditions of the Turkish people, and provided social and psychological adequacy. Traditional Turkish Houses, among the Ottoman Period in Cyprus constructed in the style of Turkish Architecture, still constitute an important element of the present day historical texture. Generally having two floors and an atrium (yard), these houses were built in adjacent form, lining down the street, and gave a style to the texture of the street with their plain facades, oriels brimming over the street, and wide fringes. Room in the Turkish Houses in Cyprus, was designed as a multi-purpose abode where day and night functions were realized, the same way it was in the tents during the nomadic life of Turks. Main room was used as the guest room, in accordance with the importance of guests in the Turkish traditions. The importance of family in the culture of Turkish life, made the hall important, as the common abode, the meeting place, into which other rooms opened. Outer halls, or colonnades, with riwaqs, enabling the house-atrium relationship, created the type of plan for the Ottoman Period houses. The staircase, connection the floors were in a position unseen from the main entrance of the house, and generally ran parallel to the hall. The atrium, or yard, has been important in the houses in Cyprus, due to the connection of Turks to nature and earth, from their past. Elements of aquatic architecture, such as well, fountain, water tank, provided the water needed for the house and yard. The formation of abodes of the Turkish Houses during the Ottoman Period in Cyprus (1570-1878) found its expression within the needs of the dwellers life culture, thus serving in accordance with the lives of the household.
Keywords: Cyprus; home; Turkish House; hall; Ottoman